X-ray radiation damage cycle of solvated inorganic ions - Bloß, Dana; Trinter, Florian; Unger, Isaak; Zindel, Christina; Honisch, Carolin; Viehmann, Johannes; Kiefer, Nils; Marder, Lutz; Küstner-Wetekam, Catmarna; Heikura, Emilia Jasmiina; Cederbaum, Lorenz S.; Björneholm, Olle; et al. (Nature Communications, 2024)
X-ray-induced damage is one of the key topics in radiation chemistry. Substantial damage is attributed to low-energy electrons and radicals emerging from direct inner-shell photoionization or produced by subsequent processes. We apply multi-electron coincidence spectroscopy to X-ray-irradiated aqueous solutions of inorganic ions to investigate the production of low-energy electrons (LEEs) in a predicted cascade of intermolecular charge- and energy-transfer processes, namely electron-transfer-mediated decay (ETMD) and interatomic/intermolecular Coulombic decay (ICD). An advanced coincidence technique allows us to identify several LEE-producing steps during the decay of 1s vacancies in solvated Mg2+ ions, which escaped observation in previous non-coincident experiments. We provide strong evidence for the predicted recovering of the ion’s initial state. In natural environments the recovering of the ion’s initial state is expected to cause inorganic ions to be radiation-damage hot spots, repeatedly producing destructive particles under continuous irradiation.